Chemistry of naturally layered manganites (invited) - Battle, P; Kasmir, N; Millburn, J; Rosseinsky, M; Patel, RT; Spring, L; Vente, J; Blundell, S; Hayes, W; Klehe, A; Mihut, A; Singleton, J (1998)
Experiments on three double-layer (n=2) Ruddlesden-Popper (RP) systems are reported. Doping Sr1.8La1.2Mn2O7 (Tc = 126 K) with Nd to form Sr1.8La1.2- xNdxMn2O7 leads to a reduction in Curie temperature for low doping levels (x = 0.2), and to behavior reminiscent of Sr1.8Nd1.2Mn2O7 for x≥0.7. This suggests that it may be possible to control the temperature of maximum magnetoresistance chemically in these phases. The application of pressure (0